Standardization of Simplicia and Ethanol Extract of Purun Danau (Lepironia articulata (Retz.) Domin) Rhizome - Arnida Arnida; Maulidia Maulidia; Amalia Khairunnisa; Sutomo Sutomo; Faisal Faisal (Borneo Journal of Pharmacy, 2021)
Purun Danau (Lepironia articulata (Retz.) Domin) has been shown to have antimalarial and antioxidant activity. This study aimed to standardize simplicia and extract of L. articulata by determining the value of its specific and non-specific parameters. A sampling of L. articulata rhizome was carried out in Guntung Manggis, Haur Gading, and Halat. The standardization method used was based on the Indonesian Herbal Pharmacopoeia and the General Standard Parameter of Extract. The organoleptic observations showed that L. articulata simplicia was reddish-brown in color, chelated taste, and had a specific odor. Microscopic observation showed parts of this plant: epidermis, cortex, endodermis, parenchyma, bundle vessels, and scalariform vessels. Ethanol-soluble extract content was 10.00-12.66%, water-soluble extract content 8.03-10.87%, drying shrinkage 7.10-7.33%, total ash content 2.03-2.52%, acid-insoluble ash 0.33-0.42%, Pb content 5.698-9.989 ppm, Cd content 0.300-0.500 ppm, Hg content 0.070-0.090 ppm. Ethanol extract of L. articulata rhizome contained alkaloids, flavonoids, tannins, glycosides, and saponins. The yield obtained was 8.05-11.23%, total ash content was 1.58-1.67%, acid-insoluble ash was 0.23-0.33%, and water content was 7.10-8.50%. Standardization of simplicia and ethanol extract of L. articulata rhizome has met the criteria.